ANALISIS POTENSI PAJAK PENERANGAN JALAN TERHADAP REALISASI PENERIMAAN PAJAK PENERANGAN JALAN DI KABUPATEN SIDOARJO - ISTIGHFARIN R, ANNISAA Istighfarin (Jurnal Akuntansi AKUNESA, 2014)
Street lighting tax is one of the existing tax in Sidoarjo, which is where its existence as a major source of local revenue or revenue ( PAD ) . The purpose of this study was to determine the contribution of the potential and actual street lighting tax owned by Sidoarjo. To calculate the tax potential street lighting is used several related variables, namely the cost and burden of the minimum cost of each class of fare. Meanwhile, to calculate tax contributions required the realization of street lighting street lighting tax and the total local tax revenue in Sidoarjo. The results showed that the potential for very large street lighting tax, well above the street lighting tax revenue realization. This comparison measurements reflected in the assessed contribution always declined from the year 2009 until the year 2013 that has not reached 100 %.Keywords: street lightening tax base, potential revenue, tax revenues street lightening.